Study on TIG Process of AZ31 Magnesium Alloy. Issue 1 (1st January 2023) - Liang, Chunping; Li, Ming; Peng, Huining; Chen, Yanyun; Li, Guochao
Abstract: In this paper, manual argon tungsten arc welding is used to weld AZ31 magnesium alloy plate with thickness of 2.5mm on both sides. The welding current parameters are changed. The best welding current is explored by analyzing the performance of welding joint; The corrosion resistance of welded joint was studied in the same medium. The results show that the microstructure of base metal zone is α- Mg solid solution, and the microstructure of the weld seam is mg solid solution α- Mg solid solution and β- Mg17 Al12 intermetallic compound. When the welding current increases from 80A to 120A, the welding heat input increases gradually, and the grain size of HAZ increases gradually. The results of microhardness test show that the microhardness of weld zone is the largest, that of base metal is moderate, and that of heat affected zone is the lowest. The corrosion resistance of AZ31 magnesium alloy welded joint shows that the corrosion resistance of the weld zone is better than that of the base metal zone.